Soft matter gradient surfaces : methods and applications - Genzer, Jan. (Hoboken, N.J. : Wiley, 2012)
'This book helps to bridge many soft material fields (materials science, chemistry, biomaterials) and introduces scientists not familiar with gradient substrates to new exciting opportunities for their work. Soft matter gradient surfaces have played a pivotal role in numerous aspects of materials research. They have facilitated fast screening of physico-chemical phenomena, enabled fabrication of material structures that would have been difficult to manufacture otherwise, acted as'recording media' for monitoring a given physico-chemico-biological process, and played a key role in designing and fabricating surface-bound'engines' capable of acting as molecular and macromolecular motors and thus drove and/or directed a given transport phenomenon. Chapters will include fabrication, gradients in self-assembled monolayers, polymer gradients, dynamic gradient structures, applications in materials science, structure and assembly, mechanical properties, sensors, biomaterial applications, protein adsorption on gradient surfaces, and cells and microtubules on gradient surfaces'--Provided by publisher.
Preface / Jan Genzer -- 1. Gradient libraries: Harnessing a ubiquitous phenomenon to accelerate experimentation / Michael J. Fasolka -- 2. Classification of key attributes of soft material gradients / Jan Genzer and Rajendra R. Bhat -- 3. Discovery and optimization of sensing materials using discrete and gradient arrays / Radislav A. Potyrailo -- 4. Colliding self-Assembly waves in organosilane monolayers / Kirill Efimenko, Ali E. Ozcam, Jan Genzer, Daniel A. Fischer, Fredrick R. Phelan, and Jack F. Douglas -- 5. Orientational anchoring of liquid crystals on surfaces presenting continuous gradients in composition / Jugal K. Gupta, Kirill Efimenko, Daniel A. Fischer, Jan Genzer, and Nicholas L. Abbott -- 6. Continuous infusion microchannel approach to generate composition gradients from viscous polymer solutions / Pratyay Basak, Pedro Zapata, Keith Reed, Ismael Gomez, J. Carson Meredith -- 7. Gradient assembly of complex surfaces for sensing, fabrication and high throughput analysis / Andrew C. Hillier -- 8. Making gradient patterns by electron beam chemical lithography with monomolecular resists / Nirmalya Ballav, Andreas Terfort, and Michael Zharnikov -- 9. Electrochemical mapping for polymer chemical and physical gradients / Roger H. Terrill, Xuejun Wang, Paul W. Bohn -- 10. Directed assembly of block copolymer films: Effects of rough substrates and thermal fields / Manish M. Kulkarni, Alamgir Karim, and Kevin G. Yager -- 11. Hydrogel gradients by self-initiated photografting and photopolymerization: Preparation, characterization and protein interactions / Tobias Ekblad, Andreas Larsson and Bo Liedberg -- 12. Polymer gradients: Responsive grafted layers / Igor Luzinov and Sergiy Minko -- 13. Bioactive self assembled monolayer gradients / Nicole M. Moore and Matthew L. Becker -- 14. Morphology gradients on different size scales, and their application in biological studies / Christian Zink and Nicholas D. Spencer -- 15. Molecularly defined peptide spacing gradient for cell guidance / Vera C. Hirschfeld-Warneken and Joachim P. Spatz -- 16. Motion of drops on gradient surfaces / R. Shankar Subramanian.
Includes bibliographical references and index.
Keywords: Functionally gradient materials; Surfaces (Technology).